GE_GERICHTE P/15831/2017 vom 10. März 2021 - GE Cour de justice (2021)
VIOL;CONTRAINTE SEXUELLE;IN DUBIO PRO REO;EXPULSION(DROIT PÉNAL);TORT MORAL | CPP.10.al3; CP.189.al1; CP.190.al1; CP.191; CP.66A.al1; CO.47